PENGARUH LOCUS OF CONTROL, PENGALAMAN KERJA, TIME BUDGET PRESSURE DAN MOTIVASI AUDITOR PADA KUALITAS AUDIT - Permana Putra, I Gede Karma Yudha; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
Factors affecting Quality Audit is the locus of control, work experience, Time budget pressure and motivation auditor.Tujuan this study was to determine the effect of locus of control, work experience, time budget pressure and motivation auditors on audit quality in the public accounting firm of Bali Province. Research tool used is multiple linear regression analysis, F test and t test. The location of this research carried out at the Bali Provincial Office Public Accountant registered in IAPI.Responden in this study were 94 auditors. The object of this study is Locus Of Control, Work Experience, Time Budget Pressure and Motivation Auditor on Audit Quality. Based on the analysis it can be concluded that the variable locus of control, work experience and motivation auditor positive effect on quality of audit.Sedangkan variable Time Budget Pressure negatively affect audit quality.
Keywords: Locus Of Control, Work Experience, Time Budget Pressure, Motivation Auditor, Quality Audit